2005
DOI: 10.1093/ajcn/81.1.243s
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and bioefficacy of polyphenols in humans. II. Review of 93 intervention studies

Abstract: For some classes of dietary polyphenols, there are now sufficient intervention studies to indicate the type and magnitude of effects among humans in vivo, on the basis of short-term changes in biomarkers. Isoflavones (genistein and daidzein, found in soy) have significant effects on bone health among postmenopausal women, together with some weak hormonal effects. Monomeric catechins (found at especially high concentrations in tea) have effects on plasma antioxidant biomarkers and energy metabolism. Procyanidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
757
2
23

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,173 publications
(794 citation statements)
references
References 103 publications
12
757
2
23
Order By: Relevance
“…In accordance with previous human studies, we observed a relatively high inter-individual variance in plasma concentration -time curves of quercetin, isorhamnetin and tamarixetin following supplementation with quercetin (15 -18) , although our non-smoking female study population was very homogenous with respect to age, baseline plasma quercetin concentrations, body weight, BMI, fat mass and fat-free mass as well as lifestyle and physical activity. This variability in plasma kinetic profiles may be attributed to inter-individual differences in digestive transit time, preferential site of absorption and enteric bacterial metabolism of quercetin as reported in the literature for quercetin and other polyphenols (3,19,20) as well as to the intrinsic solubilisation capacity of each individual.…”
Section: Discussionmentioning
confidence: 93%
“…In accordance with previous human studies, we observed a relatively high inter-individual variance in plasma concentration -time curves of quercetin, isorhamnetin and tamarixetin following supplementation with quercetin (15 -18) , although our non-smoking female study population was very homogenous with respect to age, baseline plasma quercetin concentrations, body weight, BMI, fat mass and fat-free mass as well as lifestyle and physical activity. This variability in plasma kinetic profiles may be attributed to inter-individual differences in digestive transit time, preferential site of absorption and enteric bacterial metabolism of quercetin as reported in the literature for quercetin and other polyphenols (3,19,20) as well as to the intrinsic solubilisation capacity of each individual.…”
Section: Discussionmentioning
confidence: 93%
“…The validity study did not use biomarkers because correlations between these and dietary records of flavonoid intakes are not good (r ¼ 0.35) (33) owing to their bioavailability and metabolism in the gut. (34)(35)(36) Limitations of this study include those associated with using an FFQ because FFQs are known to overestimate the true overall frequency of consumption of fruit and vegetables. (37,38) There are issues that affect the flavonoid content of foods, namely, analytical and environmental factors, processing, storage, and species differences, and these cannot be detected using a FFQ because it is a crude measure of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have shown promising, yet variable results. Consumption of isoflavones for up to a year increased expression of beneficial bone biomarkers, such as markers for bone mineral density (Williamson and Manach, 2005). On the other hand, feeding 1 mg of genistein to humans for a year did not alter bone density or bone resorption but increased markers of bone formation (Atkinson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%